Identification of Student Misconceptions on Photosynthesis Material using Three Tier Test Instrument - Defrian Melta; Putri Qalbina; Festiyed Festiyed (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2023)
Many misconceptions occur to students due to their low analytical skills. Misconceptions can occur in some courses that have abstract concepts. These concepts are difficult to understand and are interrelated with each other, so they require in-depth analysis. Analysis and in-depth understanding of biological concepts are needed in plant physiology courses. The research that has been conducted is a descriptive study with purpose to analyze and describe the level of understanding of student concepts on photosynthesis material. The subjects of this study were 30 biology education students at Padang State University (UNP) who took plant physiology classes in the 2022/2023 academic year. Students who have a good understanding of the concept are 10.87%, complete misconceptions are 23, 24%, false positive misconceptions are 22.54% and false negative misconceptions are 21.75%. These findings are expected to be used as a reference for lecturers teaching plant physiology courses to maximize concept understanding in learning.